Table of Content - - (Journal of Arabic Language Sciences and Literature, 2024)
Table of Content: 1. Unrecorded Lexis in the Annotation of the Hudhaliyyin Poems by Al-Sukkari (275 AH), from the beginning of the book to the end of Al-Mu’atal Al-Hudhali’s Poetry Mr. Shehu Yakubu Adedeji 2. The Dualism Generosity and miserliness in the dewan Ibn Himyar Al-Hamdani. cultural reading Mr. Musaddif Mousa Alnami 3. The Value of Pre-Islamic Poetry in Ibn Abd Rabbuh’s “Aleqd” and his Poetry Dr. Jamal Ali Ghidan 4. Effect of mobile learning on learning reading skills among female learners of Arabic Language as a second language Ms. Lulua Abdullh Saeed Al-Shahrani 5. Departure to ruins in pre-Islamic poetry: A study in the semiotics of emotional and existential outcome Ms. Amal Qasem Mohammed Melhi Al-Zomor, Dr. Mohd Ala Uddin Bin Othman, Prof. Elsayed Mohammed Salem 6. The Verb "Ja’ala" in the Holy Quran: A Semiotic Study of Selected Examples from the Verses of the Holy Quran Mr. Sami Hamed Al-Maliki